Energy-saving electrochemical green hydrogen production coupled with persulfate or hydrogen peroxide valorization at boron-doped diamond electrodes - Barreto, Jéssica Pires de Paiva; Santos, Jose Eudes Lima [UNESP]; Cardozo, Jussara Câmara; de Santana Souza, Domingos Fabiano; Cavalcanti, Lívia N.; Gondim, Amanda D.; Martínez-Huitle, Carlos A. [UNESP]; dos Santos, Elisama Vieira [UNESP] (Elsevier, 2024)
Persulfate (S2O82−) and hydrogen (H2) electrosynthesis has gained prominence valorization in recent times. This study reports, for the first time, a techno-economic analysis of the electrochemical boron-doped diamond (BDD)-SO42−/SO4•−/S2O82−/H2O2

H2 system. BDD is an eco-friendly material for S2O82− and H2 formation, where S2O82− is economically attractive replacements for oxygen reaction in electrochemical H2 production to valorize it as an integrated-hybrid approach. The results clearly showed that current efficiencies of up to 75.3 % and 99.4 % at 45 mA cm−2 were observed for S2O82− and H2 production with anodic accumulation of 1.77 mmol L−1 and cathodic rate 0.3 µmol min−1, respectively. A techno-economic estimation indicated a significant levelized cost of H2 (∼$ 3.78 kg−1) for this hybrid-integrated process where it was improved decreasing the anode cost or increasing the current density (j). BDD

Ni-Fe based stainless-steel (SS) mesh system could be more appropriate to be commercialized for producing persulfate and green H2, according to the techno-economic analysis. This electrochemical strategy described here is a promising green alternative to conventional processes for the simultaneous electrogeneration of oxidants and green H2, both as high value-added products.
Keywords: Diamond electrode; Green hydrogen; Levelized cost of hydrogen; Persulfate; Techno-economic study; Boron doped diamond; Electrochemicals; Levelized costs; Persulphate; Techno-Economic analysis; Techno-economic studies; Valorisation